2013
DOI: 10.1007/s00167-013-2573-1
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated landmark-based 3D analysis reveals new morphometric characteristics in the trochlear dysplastic femur

Abstract: This study shows that knee size is important in the application of absolute metric cut-off values and that the posterior femur also shows a significantly different morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 42 publications
4
55
2
Order By: Relevance
“…Recently, Van Haver et al. () found not only that the trochlear region is affected in the trochlear dysplastic femur, but that the posterior femur also has a different morphology. In addition, the geometry of the tibial plateau has been linked to the severity of trochlear dysplasia (Balcarek et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Van Haver et al. () found not only that the trochlear region is affected in the trochlear dysplastic femur, but that the posterior femur also has a different morphology. In addition, the geometry of the tibial plateau has been linked to the severity of trochlear dysplasia (Balcarek et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a morphometric analysis revealed that the trochlear dysplastic femur is also characterized by 6–8% larger posterior condyles (lateral‐medial) in the anteroposterior direction and a 6% larger medial condyle in the proximodistal direction compared with a normal femur (Van Haver et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the SSM represented changes of the sulcus angle occurring without modification in the notch width (MoV #3 in aSSM and #8 in cSSM), being this a clinical condition consistent again with dysplasia as reported in the literature . Likewise, MoV #5 in cSSM mapped notch narrowing associated to an overall enlargement of the two condylar surfaces distally, along with an increasing bump in the lateral facet, a morphologic anomaly correlated to dysplasia . Merging healthy and severe dysplastic shapes into dSSM allowed to better elucidate the association between trochlear flatness and notch width (see Figure ).…”
Section: Discussionmentioning
confidence: 55%
“…12,13 In an attempt to accurately describe the morphologic condition of the trochlear region, quantitative methods were proposed to identify morphometric indexes of the femoral geometry, such as trochlear depth, sulcus angle, lateral trochlear inclination, and trochlear facet asymmetry ratio. These indexes are computed by exploiting anatomical landmarks measured on computed tomography (CT)/magnetic resonance imaging (MRI) scans [14][15][16][17] and/or three-dimensional (3D) reconstructed shapes of the femur. [18][19][20][21][22] However, two main aspects make critical the application of such indexes to dysplastic staging.…”
Section: Introductionmentioning
confidence: 99%